2020
DOI: 10.37486/2675-1305.ec02013
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Corymbia citriodora essential oil compounds against Ascia monuste (Linnaeus, 1764) (Lepidoptera: Pieridae) and Plutella xylostella (Linnaeus, 1758) (Lepidoptera: Plutellidae)

Abstract: Essential oils (EO’s) have been investigated as a safe alternative to pest management. The toxicity of an EO can vary due to abiotic and biotic factors. The individual compounds of different EO’s have shown promise to insect control and they may present toxicity similar to or greater than the EO’s. In this study, we determined the toxicity of Corymbia citriodora EO compounds against Ascia monuste (Linnaeus, 1764) and Plutella xylostella (Linnaeus, 1758). Citronellal, trans-caryophyllene, and citronellol (LD50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In addition to citronellal, citronellol is also a fairly major compound found in E. citriodora where the concentration also varies from 5.24% [26], 10.9% [27], 12.1% [17], to 20% [16]. Previous studies that have been carried out on Ascia monuste and P. xylostella with the separate compounds in E. citriodora showed that citronellal and citronellol compounds were the most toxic compounds, where the other compounds presented lower toxicity with similar doses [20]. There are even studies that tested the compounds contained in Geranium maculatum against Pediculus humanus capitis, where even though it is often noted that complex mixtures of monoterpenoids are significantly more efficacious than the pure compound, results show that there is the greatest reduction in toxicity when citronellol is removed [29].…”
Section: Effect Of Eucalyptus On the Survival Rate Of Insect Applied ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to citronellal, citronellol is also a fairly major compound found in E. citriodora where the concentration also varies from 5.24% [26], 10.9% [27], 12.1% [17], to 20% [16]. Previous studies that have been carried out on Ascia monuste and P. xylostella with the separate compounds in E. citriodora showed that citronellal and citronellol compounds were the most toxic compounds, where the other compounds presented lower toxicity with similar doses [20]. There are even studies that tested the compounds contained in Geranium maculatum against Pediculus humanus capitis, where even though it is often noted that complex mixtures of monoterpenoids are significantly more efficacious than the pure compound, results show that there is the greatest reduction in toxicity when citronellol is removed [29].…”
Section: Effect Of Eucalyptus On the Survival Rate Of Insect Applied ...mentioning
confidence: 99%
“…Eucalyptus is currently one of the essential oils that is often used as an insecticide [14,15]. One type of eucalyptus, Eucalyptus citriodora, has been tested several times and proven to be quite effective against several types of insects, namely Anopheles gambiae [16], Aedes aegypti [17], Tribolium castaneum [18], Myzus persicae [19], Frankliniella schultzei [19], Plutella xylostella [20], Sitophilus oryzae [21], Lutzomyia longipalpis [22], termites [23], and Periplaneta americana [24]. However, currently not much information has been found regarding the testing of E. citridora against D. bisaltidae, so that in this study it will be studied further.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies are showing that E. citriodora has an insecticidal activity in several types of insects such as Lutzomyia longipalpis (Maciel et al, 2010), Periplaneta americana (Manzoor et al, 2012), Z. subfasciatus (Franca et al, 2012), Anopheles gambia (Bossou et al, 2013), Myzus persicae (Costa et al, 2015), Frankliniella schultzei (Costa et al, 2015), Tenebrio molitor (Salazar et al, 2015), Tribolium castaneum (Bossou et al, 2015), S. oryzae (Tamgno et al, 2019), Aedes aegypti (Manh et al, 2020), Ascia monuste (Santos et al, 2020), Plutella xylostella (Santos et al, 2020), and S. zeamais (Ataide et al, 2022), E. citridora essential oil was recorded to cause 100% mortality of Z. subfasciatus (Franca et al, 2012) and A. gambiae (Bossou et al, 2013). The E. citriodora used on A. gambiae in the research came from Benin, which contains citronella, citronellol and isopulegol as its main compounds.…”
Section: Insecticidal Activitymentioning
confidence: 99%
“…In the research conducted by Santos et al (2020), the compounds contained in E. citriodora were tested separately. The results showed that citronellal and citronellol were the most toxic compounds because they showed the lowest lethal doses for A. monuste and P. xylostella.…”
Section: Insecticidal Activitymentioning
confidence: 99%